Forum Panelist 2: MODA: Protecting Malaysia’s Frontliners, One Stitch at a Time - Looi, Melinda (International Journal of Human and Health Sciences (IJHHS), 2021)
When COVID-19 brought on the MCO or Movement Control Order in March 2020, it was an unprecedented & uncertain time for Malaysians. As the battle to treat infections began, the issue of personal protective equipment (PPE) arose. Shortage of availability, high cost, suitability of materials were the challenges faced by our medical frontliners and to which MODA decided to step up to fill the gap.MODA is a Non-Profit Organization (NPO) whose members comprise local fashion designers as well as persons & companies involved in Malaysia’s fashion industry. Thus, began a mission to raise funds, procure suitable locally produced material, mobilize manpower from designers with staff & facilities to produce PPE, to individual volunteers who cut, sew, packed & transported completed PPE to hospitals throughout the country.However, while this initiative addressed Malaysia’s needs currently, it is a short-term solution. In this article, we wish to not only share MODA’s experience in producing PPE but look ahead towards a solution for the future. Reusable PPE that will reduce the massive amount of waste, suitable materials that can be produced locally and is suitable for our climate, a PPE bank and storage facilities so that we are better prepared should another pandemic arise. Together let us learn from this experience and face the future better prepared as a nation! International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S7